UTILIZATION OF TREATED WOOD ,STEEL, FIBREGLASS, FERROCEMENT AND ALUMINIUM IN THE CONSTRUCTION OF MORDERN FISHING BOATS AND THEIR COMPARATIVE COST ANALYSIS - RALASUBRAMANYAN, R (Fishery Technology, 2016)
Modern fishing boats have to be built not only on perfectJines but also with sound and strong construction materials thatwill ensure a long lasting trouble free service commensurate withthe heavy capital investment involved. Choice of constructionmaterials for fishing boats need careful scrutiny as they have toperform too well under most aggressive environments- sea-waterand marine atmosphere. A number of alternative boat-buildingmaterials are now available whose comparative merits and demeritsas well as comparative costs are brought out in this paper.